RPA quasi-elastic responses in infinite and finite nuclear systems - Bauer, Eduardo (2001)
Quasi-elastic responses in nuclear matter and in ¹²C and ⁴⁰Ca nuclei are calculated in ring approximation to investigate the finite size effects on the electromagnetic quasi-elastic responses. A method to simulate these effects in infinite systems calculations is proposed. The sensitivity of the results to the various terms of the residual interaction is studied. The results of nuclear matter RPA calculations are compared with those obtained in ring approximation to evidence the importance of the exchange terms.